A portrayal of the history Antong Coffee Factory in Taiping, Perak through mural - Merman, Hairulnisak; Tagie, Gladys; W. Mohd Apandi, Wan Nurhasyima; Saad, Mohd Nafis (Universiti Teknologi MARA, Perak, 2025)
Mural painting is a form of art that is very effective in conveying information through pictures. The nature of mural paintings that can be appreciated by large groups of society makes it an alternative to mass communication in conveying and disseminating information that encompasses various social, historical, political, or cultural contexts. This study was made to analyze the visuals depicted on the mural paintings on the walls of the Antong Factory. The study method used in this study was to use qualitative methods. Researchers obtain information through primary data methods such as interviews and observations and use secondary methods derived from data sources such as journals, newspaper clippings, and websites. The results showed that the mural painting is not only a wall decorator but also an opportunity for visitors to observe the creative beauty produced as well as to convey information on the history of the establishment of the Atong Factory. Subsequently, through the mural painting, the mural was also indirectly promoted to the local and external communities. It is hoped that the mural will be able to convey accurate historical information to the target especially the younger generation to have the ability to evaluate mural paintings and add aesthetic knowledge value.